Editorial: Should child and adolescent mental health professionals be diagnosing personality disorder in adolescence? - Elvins, Rachel; Kaess, Michael (Child and adolescent mental health, 2022)
Diagnosing personality disorders in adolescence remains a contentious issue, particularly in the United Kingdom (UK). In this debate section we hear from clinicians, service users and family members on this topic; strongly held views are expressed and evidenced.
Gesehen am 13.07.2022